Asthma knowledge and management practices of pharmacists in Greater Accra - Atiemo, Mawuli; Wutor, Victor Collins; Ayisi-Boateng, Nana Kwame; Banga N’Guessan, Benoit (International Journal Of Community Medicine And Public Health, 2025)
Background: Asthma continues to be a global public health problem, and community pharmacists are at the center of drug therapy in areas such as Greater Accra, Ghana. Methods: This study determined what 177 community pharmacists knew about managing asthma and what barriers they faced in their practice. Data were collected using a structured questionnaire regarding demographics, asthma knowledge, daily management practices, and perceived barriers. Results: Most pharmacists (55.93%) had a good understanding of asthma management, 42.37% had moderate knowledge, and 1.69% had poor knowledge, the results showed. More specific to asthma were pharmacists (100%), were well versed in asthma pathophysiology (100%), triggers (93.22%), and use of peak expiratory flow (PEF) meters (94.92%). However, some inconsistencies in practice were present. While inhalation techniques were assessed by 73.68%, treatment side effects were discussed by 79.31%; however, only 49.15% were routinely counselled on inhaled corticosteroids (ICS). In addition, only 18.64 percent ensured patients had written asthma action plans. Asthma Action Plans were lacking in 81.4%; there were inadequate training opportunities (64.4%); designated consultation areas were lacking (52.5%); pharmacists had insufficient time to care (52.5%) and had time constraints to care (55.9%). Our findings are consistent with global observations and highlight system-level challenges that impede effective asthma management. Conclusions: Although the Greater Accra pharmacists are knowledgeable enough based on their low rates of noncompliance indicated by their blood pressure scores, we believe that gaps in their practices and barriers to narrowing these gaps must be bridged.